2007
DOI: 10.1016/j.ydbio.2007.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of Notch signaling in cochlear development

Abstract: Notch signaling inhibits hair cell differentiation, based on studies on mice deficient in Notch signaling-related genes and its downstream genes. However, the precise mechanisms of this inhibition are unknown because it is difficult to control the timing and duration of the suppression of Notch signaling. Here, we developed a novel in vitro culture and analysis method for mouse fetal cochleae and examined the roles of Notch signaling by its reversible inhibition through the use of Notch signaling inhibitors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 40 publications
7
90
3
Order By: Relevance
“…The Notch pathway is of particular interest because experimental down-regulation of Notch induces transdifferentiation of mammalian support cells into hair cells (30,(52)(53)(54)(55)(56)(57). In contrast to previous reports in zebrafish and chicken (9, 13), our SPIA pathway analysis suggested that the Notch pathway is inhibited immediately after hair cell death because of simultaneous upregulation of numb (Fig.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…The Notch pathway is of particular interest because experimental down-regulation of Notch induces transdifferentiation of mammalian support cells into hair cells (30,(52)(53)(54)(55)(56)(57). In contrast to previous reports in zebrafish and chicken (9, 13), our SPIA pathway analysis suggested that the Notch pathway is inhibited immediately after hair cell death because of simultaneous upregulation of numb (Fig.…”
Section: Resultscontrasting
confidence: 79%
“…A growing number of studies have explored how the manipulation of Notch signaling could aid in regenerating mammalian hair cells. It is well established that the inhibition of Notch signaling causes an increase in the number of hair cells in uninjured and injured chicken, guinea pig, and mouse utricles and cochleae and in injured zebrafish ears and lateral line neuromasts (52,53,(55)(56)(57)88). The presence of Notch is detrimental to hair cell differentiation, because it blocks the proneural gene atoh1a and thereby maintains support cells (9,13,65,89,90).…”
Section: Notch Signaling Is Down-regulated Early In Lateral Line Hairmentioning
confidence: 99%
“…During embryonic development, activation of Notch signaling within a subset of prosensory cells inhibits the activation of a HC-specific program, limiting these cells to a SC fate (51)(52)(53). Inhibition of Notch signaling using γ-secretase inhibitors results in the generation of new HCs within the embryonic and neonatal murine cochlea (54)(55)(56); although the ability of SCs to dedifferentiate and convert to a HC fate declines rapidly within the first postnatal week of life. In the adult animal, only SCs located in the cochlear apex respond to Notch inhibition and infrequently convert to a HC fate (57).…”
Section: Lin28b Overexpression Results In a Delay In Prosensory Cell mentioning
confidence: 99%
“…More significant hair cell overproduction phenotypes in cochlea that carried mutations in both Jag2 and Dll1 indicate that there is synergistic function between ligands, and loss of one Notch ligand in hair cells can be compensated by others (Kiernan et al, 2005). Therefore, Dll3 compensation could account for the mild phenotypes observed in Dll1 and Jag2 lossof-function studies as compared with Notch1 mutation or Notch inhibition experiments (Lanford et al, 1999;Yamamoto et al, 2006;Takebayashi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…First, conditional Notch1 mutations in the otic epithelium of FoxG1-Cre Notch flox/Ϫ mice resulted in a far more dramatic increase in hair cell numbers than that observed in the Dll1 hyp/Ϫ Jag2 Ϫ/Ϫ cochlea (Kiernan et al, 2005). Second, severe hair cell overproduction phenotypes were observed in cochlear explants treated with Notch1 antisense oligonucleotides or pharmacological inhibitors of Notch signaling (Zine et al, 2000;Yamamoto et al, 2006;Takebayashi et al, 2007). As noted above, there are additional Notch ligands, and their expression has not previously been described in the developing cochlea.…”
Section: Introductionmentioning
confidence: 99%